The art of being deaf : a memoir - McDonald, Donna, 1955- (Washington, DC : Gallaudet University Press, 2014)
Growing up in Australia in 1950s as the only deaf child in a family of five, McDonald did not consider her deafness to be "remarkable" but "just the way things were." She attended a school for the deaf until she was eight years old, when she re-enrolled at the local school because her mother wanted her to be "normal." Trying to bridge two worlds for much of her life, McDonald, who never felt defined by her disability, now realizes that she gained as much as she lost. Much of the book is devoted to McDonald's conversations with people who had a significant role in her life, but she also includes a thoughtful layer informed by cultural portrayals in both fiction and nonfiction that are deftly interweaved with moments from her personal life. Although there are segments that will tug at a reader's heart, this is no tearjerker; rather, it is a personal and informative look at "deaf lives as told by deaf people.
Deaf -- Reunions -- Wrong snow -- A great big wash of tears -- Talk speak words sign -- A six-month plan -- Music lessons -- But my eyes still see -- In the beginning was the word -- The best of both worlds -- Work -- Talking about deafness -- Falling for his line -- Will i still be deaf when i grow up? -- Shattered -- All grown up now -- A reluctant memoirist -- Epilogue : the sleeper awakes.
Includes bibliographical references.
Keywords: McDonald, Donna, -- 1955-.; Deaf -- Australia -- Biography; Deaf women -- Australia -- Biography